Silvicultures Management and Conservation - Allende Álvarez, Fernando; Gomez-Mediavilla, Gillian; López-Estébanez, Nieves (IntechOpen, 2019)
The history and past management of trees within woodlands are the main objectives of this book. The authors show four points of view about one theme: silvicultures. Wood pasture systems of South East England and Northern Italy, Spanish pollard forests, and Portuguese montado are great examples of European ancient forests. Reconstruction of forest ecology, management, protection, and the understanding of these silvicultures from different perspectives are the main values of this monograph. The authors would like to make all readers aware of the value of ancient forests as cultural and socioecosystem services.